(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Ability to use modern information technologies; communication with the artificial intelligence system, dialogic communication in the "hybrid intelligence" man-machine system, telematics tools, processes of using global and local information and computing networks were studied.